Hubungan Dukungan Petugas Kesehatan Terhadap Perilaku Individu dalam Pemanfaatan Layanan BPJS - Irma Finurina Mustikawati; Endang Sutisna Sulaeman; Achmad Arman Subijanto; Suminah Suminah (Syntax Corporation Indonesia, 2023)
Economic development's primary goal is to make the community prosperous. EBSCO, ScienceDirect, and Proquest databases are used for both international and domestic literature searches. In the initial rounds of looking for journal articles, we discovered 25 papers between 20 and 22 using the keywords